2005
DOI: 10.1002/lt.20389
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation for severe hepatic graft-versus-host disease: An analysis of aggregate survival data

Abstract: Graft-versus-host disease (GVHD) often occurs after bone marrow transplantation (BMT). GVHD may lead to cirrhosis or complete destruction of the bile ducts, and few effective treatment options exist for such cases. Orthotopic liver transplantation (OLT) has been described as an option, but to date the patient survival, graft survival, and GVHD recurrence rates after OLT have been unknown. Cases of OLT for GVHD were accumulated from several sources: (1) cases of OLT performed at a single institution, (2) the En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…Numerous case reports describe the success of SOT after HSCT (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) …”
Section: Discussionmentioning
confidence: 99%
“…Numerous case reports describe the success of SOT after HSCT (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, at this stage, there is no established therapy other than liver transplantation. Some studies have reported successful liver transplantation from alive or deceased donors for intractable hepatic GVHD after HCT (17)(18)(19). Increased risk of relapse as a result of life-long immunosuppression after solid organ transplantation might be a major concern especially in highrisk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of chronic GVHD with corticosteroids and other immunosuppressants is less effective than such treatment for acute GVHD. Interestingly, orthotopic liver transplantation for severe GVHD is associated with a surprisingly high 5-year survival rate (62.9%) and lack of GVHD recurrence [36].…”
Section: Graft-versus-host Diseasementioning
confidence: 99%